Reimagining Australia at the Cosmopolitan Intersection - Watson, Greg (Universitat de Barcelona, Observatori: Centre d' Estudis Australians i Transnacionals / The Australian and Transnational Studies Centre, 2018)
Living with difference is an unavoidable part of living in Australia. How we live with difference, therefore, impacts how people imagine and reimagine Australia. This paper considers the matter of reimagining Australia as a phenomenon that is located within the microecology of our everyday urban spaces. It is interested in knowing about these spaces and how they can contribute to the reimagining of Australia at the microlevel of society. It considers two examples of spaces that engage people in this task and advances the notion of the cosmopolitan intersection, framing reimagining within Anthony Kwame Appiah’s vision of cosmopolitanism and Jean-Luc Nancy’s vision of coexistence.